2016
DOI: 10.1186/s12861-016-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

Late stage definitive endodermal differentiation can be defined by Daf1 expression

Abstract: BackgroundDefinitive endoderm (DE) gives rise to the respiratory apparatus and digestive tract. Sox17 and Cxcr4 are useful markers of the DE. Previously, we identified a novel DE marker, Decay accelerating factor 1(Daf1/CD55), by identifying DE specific genes from the expression profile of DE derived from mouse embryonic stem cells (ESCs) by microarray analysis, and in situ hybridization of early embryos. Daf1 is expressed in a subpopulation of E-cadherin + Cxcr4+ DE cells. The characteristics of the Daf1-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Adhesion strength of differentiated fibroblast has been known to be stronger than those of iPSCs ( Yu et al., 2018 , i.e., F iPSC < F MC ). In contrast, adhesion strength of late stage definitive endodermal cells showed gradual decreases according to the specific integrin subtypes ( Ogaki et al., 2016 , i.e., F HE < F iPSC ). Although both studies support the obtained order of adhesion strength, further studies are necessary to provide the conclusive answer.…”
Section: Resultsmentioning
confidence: 88%
“…Adhesion strength of differentiated fibroblast has been known to be stronger than those of iPSCs ( Yu et al., 2018 , i.e., F iPSC < F MC ). In contrast, adhesion strength of late stage definitive endodermal cells showed gradual decreases according to the specific integrin subtypes ( Ogaki et al., 2016 , i.e., F HE < F iPSC ). Although both studies support the obtained order of adhesion strength, further studies are necessary to provide the conclusive answer.…”
Section: Resultsmentioning
confidence: 88%
“…The synthesized cDNA was used as a template for qPCR, which was performed using a SYBR Green real-time PCR Master Mix (TOYOBO, Osaka, Japan). The primers used for the undifferentiated cells, DE marker genes and hXIST RNA are shown in S1 Table [ 3 , 7 , 14 , 17 , 18 ]. PCR and data analyses were performed on an Applied Biosystems StepOne Plus real-time PCR system (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we cultured the most widely used female hiPSC lines 201B7 and 253G1 [ 3 , 12 ] on SNL and MEF to evaluate their undifferentiated state and efficiency of differentiation into DE, depending on the type of feeder cell used. We found that the mRNA and protein expressions of the DE marker genes of the sex-determining region Y-box 17 (SOX17) and Forkhead box A2 (FOXA2) and the expressions of the DE surface marker C-X-C chemokine receptor type 4 (CXCR4) [ 7 , 13 , 14 ] were lower in the DE cells induced from 201B7 and 253G1 cells cultured on SNLs than in those induced from 201B7 and 253G1 cells cultured on MEFs under culture conditions employed for DE differentiation. These results suggested that undifferentiated culture of hiPSCs on SNLs inhibited DE differentiation when compared with MEFs.…”
Section: Introductionmentioning
confidence: 99%